2021
DOI: 10.1186/s43162-021-00036-1
|View full text |Cite
|
Sign up to set email alerts
|

Serological detection of hepatitis B and D virus co-infection among patients attending a tertiary health facility at Maiduguri, Nigeria

Abstract: Background Hepatitis D virus (HDV) is highly pathogenic, and clinical studies revealed that HDV infection aggravates the natural history of the underlying hepatitis B virus (HBV) infection by progression to cirrhosis that leads to early decompensation of liver function compared with HBV mono-infection. To determine the seroprevalence of HDV among HBsAg-seropositive patients and associated biochemical profiles at Maiduguri, Nigeria, a hospital-based cross-sectional study on 180 sera of patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 46 publications
0
0
1
Order By: Relevance
“…These findings are similar to what was reported by a previous study which also reported higher HDV prevalence among female liver disease patients in Botswana, but without statistical significance [15] . These two findings suggest that gender might not be a risk factor for HDV infection, which is contradictory to other studies which have reported higher HDV prevalence in males [25] , [26] , [27] . The exact reason(s) for the reported high HDV prevalence in either gender are yet to be elucidated.…”
Section: Discussioncontrasting
confidence: 99%
“…These findings are similar to what was reported by a previous study which also reported higher HDV prevalence among female liver disease patients in Botswana, but without statistical significance [15] . These two findings suggest that gender might not be a risk factor for HDV infection, which is contradictory to other studies which have reported higher HDV prevalence in males [25] , [26] , [27] . The exact reason(s) for the reported high HDV prevalence in either gender are yet to be elucidated.…”
Section: Discussioncontrasting
confidence: 99%
“…In Nigeria, the prevalence of HBV/HIV coinfection varies across different regions [10][11][12][13][14][15][16][17]. While several studies have investigated the burden of HBV/HIV co-infection in other populations, there is a significant knowledge gap concerning pregnant women.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Although, the exact prevalence of HDV infection cannot be predicted due to absence of standard screening procedures and inaccessibility in some resources limited countries but in a recent analysis, 13% to 14% which corresponds to 62 to 72 million people were found to be infected with HDV worldwide. 4 According to World Health Organisation (WHO) 5% of HBsAg carriers worldwide are infected with HDV. 5 HDV is a single stranded defective RNA virus which needs Hepatitis B virus (HBV) for completion of its replication cycle inside the host cells.…”
Section: Introductionmentioning
confidence: 99%
“…Though HDV is considered to be imperfect and requires HBV to be human pathogen, HDV is considered to be most severe and rapidly progressive form of chronic hepatitis. 4 Infection with HDV and HBV viruses can occur in two ways: it can happen simultaneously, co-Background: Hepatitis Delta virus (HDV) is a small RNA virus responsible for causing both acute and chronic liver disease in persons infected with Hepatitis B. Chronic HDV infection worsens the preexisting HBV-related liver damage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation